2016
DOI: 10.1016/j.jnucmat.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

High-flux He+ irradiation effects on surface damages of tungsten under ITER relevant conditions

Abstract: A large-power inductively coupled plasma source was designed to perform the continuous helium ions (He +) irradiations of polycrystalline tungsten (W) under International Thermonuclear Experimental Reactor (ITER) relevant conditions. He + irradiations were performed at He + fluxes of 2.310 21-1.610 22 /m 2 s and He + energies of 12-220 eV. Surface damages and microstructures of irradiated W were observed by scanning electron microscopy. This study showed the growth of nano-fuzzes with their lengths of 1.3-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 18 publications
(48 reference statements)
1
25
0
Order By: Relevance
“…Polycrystalline W (Honglu, Xiamen) with a size of 1cm×1cm×2mm was used as the specimen. To generate the W nano-fuzzes, the polished W specimen was irradiated with low-energy (200eV) and large-flux (1.3×10 22 /m 2 ⋅s) He + plasmas in our LP-MIES system described previously [7,12]. The radio frequency power of 7.5kW was injected into the inductively coupled plasma (ICP) source, resulting in W surface temperature of 1480°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polycrystalline W (Honglu, Xiamen) with a size of 1cm×1cm×2mm was used as the specimen. To generate the W nano-fuzzes, the polished W specimen was irradiated with low-energy (200eV) and large-flux (1.3×10 22 /m 2 ⋅s) He + plasmas in our LP-MIES system described previously [7,12]. The radio frequency power of 7.5kW was injected into the inductively coupled plasma (ICP) source, resulting in W surface temperature of 1480°C.…”
Section: Methodsmentioning
confidence: 99%
“…Kajita proposed that the formation and growth of W nano-fuzzes can be attributed to the diffusion and coalescence of He nano-bubbles at an elevated temperature [6]. Our previous study indicates that the diffusion and coalescence of He atoms in W surface layer can control the growth and structure of nano-fuzzes [7]. Coral-like or tree-like nano-fuzzes can be formed due to low-energy He + irradiation, depending on the energy and flux of He ions.…”
Section: Introductionmentioning
confidence: 93%
“…The irradiation parameters deployed in this study can be found in Table 1. More details regarding the equipment used can be found from our previous publications [26,27]. Two other typical dyes commonly used in the industry, namely X-BR and X-3B, were also characterized following the same procedures.…”
Section: Fabrication Of Sers Substratementioning
confidence: 99%
“…Compared with commercial W, the surface of the W-TiC composite exhibits different damage behaviors after He-ion irradiation. Liu et al [27] found that the dense nano-fuzz was formed uniformly on the surface of W at the He-ion energy of > 70 eV or He-ion fluxes of > 1.3 × 10 22 He + m −2 s −1 . Al-Ajlony et al [28] found that the dense and tangled fuzz structure was formed on the surface of W with a high He-ion fluence of 9.2 × 10 24 He + m −2 .…”
Section: He-ion Irradiationmentioning
confidence: 99%